Features of Lymph Node Metastasis and Structural Recurrence in Papillary Thyroid Carcinoma Located in the Upper Portion of the Thyroid: A Retrospective Cohort Study - Heng, Yu; Feng, Siqi; Yang, Zheyu; Cai, Wei; Qiu, Weihua; Tao, Lei (Frontiers in Endocrinology, 2022)
Background: This study aims to reveal the features of lymph node metastasis (LNM) and recurrence in PTC tumors located in the upper portion of the thyroid. Methods: A total of 1075 PTC patients were retrospectively reviewed, including 314 patients with a tumor in the upper portion of the thyroid. Results: The results showed no difference between the patients with a tumor in the upper portion of the thyroid and those with a tumor in the non-upper portion in terms of LNM, including both central LNM (CLNM) and LLNM. However, patients with a tumor in the upper portion were significantly more prone to LLNM and exhibited a significantly worse recurrence outcome than those with a tumor in other subregions. Multivariate analysis showed that four factors—age no more than 40, maximum tumor diameter no less than1.0 cm, the presence of thyroid capsular invasion, and tumor with ipsilateral nodular goiter—were independent risk factors for LLNM of the tumor in the upper thyroid. A predictive risk-scoring model was established based on these factors. Conclusions: Patients with PTC located in the upper portion may have an exclusive lymphatic drainage pathway to the lateral neck region and are more prone to suffer from LLNM and tumor recurrence than those with a tumor located in other subregions. A new postoperative strategy selection flow chart was established based on our newly created risk-scoring model that can effectively predict the individualized possibility of occult LLNM for PTC patients with a tumor in the upper portion.